2SPD-027 Economic impact of drug shortages. (24th March 2020) - Aparicio Carreño, C; Labeaga Beramendi, Y; Rodriguez, B; Fernández González, B; Gándara Ande, A; Barbazán Vázquez, FJ; Martínez-Múgica Barbosa, C; Durán Román, C
Abstract : Background and importance: Drug shortages is an international problem, which is increasingly frequent, and has a huge impact on healthcare systems. Aim and objectives: To quantify the economic implications of drug shortages in acute care hospitals. Material and methods: A retrospective descriptive study was conducted from January 2018 to March 2019. Shortages were defined as shortcomings in the supply of a medicinal product that affected the patient's ability to access the required treatment in due time. Costs from management of drug shortages were calculated as the difference between the acquisition cost of the original medicine immediately prior to its start and the alternative drug (bought from compounding pharmacies when raw material was available or temporarily imported when it was still available in other countries in the EU). Results: During the study period, 11 medicines were involved in drug shortages (table 1 ). There were 19 new suppliers: 5 were compounding pharmacies and 14 were international manufacturers. An alternative drug with the same active substance was imported in all cases but 1, dexchlorpheniramine injection 5 mg, which was switched to an equivalent drug (chlorpheniramine injection 10 mg). All alternatives caused an increase in the price of acquisition compared with the original medicine, except for two (intravesical BCG and one of the alprostadil suppliers), where the price remained unaltered. The average increase in price was 4.28€ per unit (range 0–25€) which represented an average increase of 409.2%. Total cost of purchases due to shortages was 91 551.13€ (79% accounting for the acquisition of three drugs: alprostadil, chlorpheniramine and piperacillin/tazobactam). This resulted in an increase of 67 607.19€ on the hypothetical price calculated from regular suppliers. Conclusion and relevance: The results suggest that shortages significantly increase the acquisition cost of pharmaceuticals in hospitals. Strategies to minimise the effects of drug shortages should be implemented. References and/or acknowledgements: No conflict of interest.